2022
DOI: 10.1111/1742-6723.13979
|View full text |Cite
|
Sign up to set email alerts
|

Continued opioid use following an emergency department presentation for low back pain

Abstract: Objective To investigate the proportion of patients with low back pain who receive an opioid analgesic prescription on hospital discharge, the proportion using opioid analgesics 4 weeks after discharge, and to identify predictors of continued opioid analgesic use at 4 weeks after an ED presentation in opioid‐naïve patients. Methods An observational cohort study nested within a randomised controlled trial in four EDs in New South Wales, Australia. Participants were adults who presented to the ED with non‐specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Seven of the 72 included studies [ 56 , 59 , 60 , 62 , 71 , 80 , 87 ] were scored at a high overall risk of bias (eTable 3); all investigated opioid-related adverse events. More than one-third of included studies (25 studies) [ 35 , 36 , 45 , 47 , 51 , 53 , 56 , 57 , 59 , 62 , 63 , 67 , 71 , 73 , 75 , 77 , 80 , 85 , 87 , 88 , 90 , 92 , 94 , 95 , 101 ] were considered as having high or unsure risk of attribution bias due to the lack of reporting of loss to follow-up in randomised controlled trials or data completion rate not reported in observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the 72 included studies [ 56 , 59 , 60 , 62 , 71 , 80 , 87 ] were scored at a high overall risk of bias (eTable 3); all investigated opioid-related adverse events. More than one-third of included studies (25 studies) [ 35 , 36 , 45 , 47 , 51 , 53 , 56 , 57 , 59 , 62 , 63 , 67 , 71 , 73 , 75 , 77 , 80 , 85 , 87 , 88 , 90 , 92 , 94 , 95 , 101 ] were considered as having high or unsure risk of attribution bias due to the lack of reporting of loss to follow-up in randomised controlled trials or data completion rate not reported in observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study of patients presenting to ED with low back pain suggests 31.7% (95% CI 22.9 to 41.6) 34 received opioid prescription at discharge and 30.3% (95% CI 23.7 to 38.0) received non-indicated lumbar imaging. 35 To detect an effect of the patient nudges or clinician nudges on the number and proportion of encounters involving low-value care, with an absolute difference of 10% (eg, event rate 30% in the control hospitals vs event rate 20% in intervention hospitals) and with 80% power, alpha set at 0.05, assuming an intraclass correlation coefficient (ICC) of 0.10 and an intraperiod correlation (IPC) of 0.09 (ie, between the before and after periods, within each site) and accounting for variable cluster sizes, we would require 2416 encounters for back pain due to a musculoskeletal condition across 8 sites, over a 9-month trial period (ie, ~302 encounters per site, over 3-month baseline and 6-month intervention period).…”
Section: Methods and Analysismentioning
confidence: 99%
“…There is widespread agreement on the limited use of opioids and their detrimental long-term effects. Despite recommendations against first-line use of opioids, however, there is a broad acknowledgment of overprescription and chronic use of opioids for patients in emergency departments [ 18 ] and following discharge [ 26 ]. We found no consensus on the reason for this discrepancy.…”
Section: Reviewmentioning
confidence: 99%